Analisis Pengaruh Peluang Dan Tantangan Dalam Pengembangan Teknologi Pertanian Di Era Revolusi Industri 4.0 Terhadap Hasil Produksi Padi Di Musi Rawas - Syabawaihi, Syabawaihi; Nur Annisa, Febrina; Analisa, Widya (Universitas PGRI Palembang, 2024)
The goal of this investigation This study's focus is on how the industrial revolution unfolded. This journal's discussion of the elements influencing the growth of the industrial revolution is on how rice production affects the extent to which PTT and SRI technology is applied. This study aims to define and comprehend the effects of the industrial revolution. The purpose of this study is to determine variable values without developing, comparing, or seeking for correlations. It employs a single descriptive qualitative methodology. In this study, the sample method was purposeful sampling. A technique referred to as